Assessment of obesity stigma and discrimination among Spanish subjects with a wide weight range: the OBESTIGMA study - Sánchez, Enric; Ciudin, Andreea; Sánchez, Ana; Gutiérrez-Medina, Sonsoles; Valdés, Nuria; Flores, Lilliam; Marí-Sanchis, Amelia; Goñi, Fernando; Sánchez, Marta; Nicolau, Joana; Muñoz, Concepción; Díaz-Trastoy, Olaia; et al. (Frontiers in Psychology, 2023)
Introduction: This study aims to assess the extent of rejection and instances of stigmatization linked to obesity within the Spanish population, encompassing a diverse spectrum of weights ranging from normal weight to morbid obesity. Additionally, the study seeks to identify the primary factors influencing these experiences and further examines the impact of bariatric surgery on such dynamics. Materials and Methods: Multicenter observational study with involving a total of 1,018 participants who were recruited from various Obesity Units. Negatives attitudes towards people with obesity were assessed through three questionnaires: (i) Antifat Attitudes Scale (AFA), (ii) Stigmatizing Situations Inventory (SSI) and (iii) Weight Bias Internalization Scale (WBIS). Subjects were categorized into four groups based on their BMI and history of prior previous bariatric surgery. Results: The cumulative score across all questionnaires (AFA, SSI and WBIS) exhibited a progressive increase, from participants with normal weight to those with obesity (P<.001 for all). Within the AFA questionnaire, males showed more rejection towards people with obesity than women, also perceiving obesity as a disease linked to a lack of willpower (P=.004 and P=.030, respectively). The overall SSI score was negatively associated with age (r=-.080, P=.011), with young participants encountering more stigmatizing experiences than their adults counterparts. Neither employment status nor educational demonstrated a significant association with any of the questionnaires. Interestingly, patients who underwent lost weight following bariatric surgery did not exhibit improved outcomes. Conclusion: Individuals with obesity demonstrate a heightened level of aversion towards the disease compared to those with normal weight. Concurrently, the incidence of stigmatizing encounters displays a concerning escalation among younger individuals.